(untitled) (Journal of Pathology of Nepal, 2011)
Background: Chronic kidney disease is usually associated with anemia and the level of anemia correlates with the severity of renal failure. This study was carried out to evaluate the profile of anemia and to find the correlation between the severity of anemia and serum creatinine levels in predialysis and postdialysis Chronic kidney disease patients. Materials and Methods: A cross-sectional study was conducted in 40 chronic kidney disease patients in the department of pathology and nephrology, KIST Medical College. Hemoglobin, hematocrit, red cell indices, peripheral blood smears and serum creatinine levels were examined using standard techniques. Results: There was a significant difference in the hemoglobin and hematocrit levels in predialysis and postdialysis patients (P <0.005). All 40 patients (100%) were anemic. Although moderate anemia was most common in both groups of patients, severe anemia was more common in postdialysis patients (5% in predialysis and 15% in postdialysis patients). The peripheral blood smear examinations showed that normocytic normochromic anemia was most frequent (90% in predialysis and 77.5 % in postdialysis patients). There was no significant correlation between the severity of anemia and serum creatinine levels (P > 0.05), r=-0.14 and -0.17 in predialysis and postdialysis group respectively. Conclusion: The most frequent anemia in chronic kidney disease patients was normocytic and normochromic type of a moderate degree. Significant correlation was not found between the severity of anemia and serum creatinine levels in both pre and postdialysis group of patients. Keywords: Chronic Kidney Disease; Anemia; Creatinine; Hemoglobin; Hematocrit; Hemodialysis DOI: 10.3126/jpn.v1i1.4446 Journal of Pathology of Nepal (2011) Vol.1, 26-29